PMBOK y PRINCE 2 similitudes y diferencias - Fernández-Parra, Kenia; Garrido-Saroza, Ariannys; Ramírez-Martínez, Yosvani; Perdomo-Bello, Isamira (Revista Científica, 2015)
There are different standards focused on project management. Examples of these standards are the PMBOK Guide and PRINCE2 method. In this paper, it is made a comparative analysis of the PMBOK Guide in relation to PRINCE2 structured method, based on the assessment of different literature sources. During the course of the investigation, different theoretical elements of both PMBOK and PRINCE2 were analyzed, such as the origin, evolution, structure, and application, allowing the identification of similarities and differences between them. The result of this research reveals that these standards are not considered mutually exclusive and that can coexist on the same project. PRINCE2 determines what, how, when and by whom the activities will be implemented using a common language easily assimilated and PMBOK is an international reference guide that incorporates a wide range of knowledge about project management.